The model as performance : staging space in theatre and architecture - Brejzek, Thea; Wallen, Lawrence (Performance + design., 2018)
"'The model as performance' investigates the history and development of the scale model from the Renaissance to the present. Employing a scenographic perspective and a performative paradigm, it explores what the model can do and how it is used in theatre and architecture. The volume provides a comprehensive historical context and theoretical framework for theatre scholars, scenographers, artists and architects interested in the model's reality-producing capacity and its recent emergence in contemporary art practice and exhibition.